Clinical core of the Alzheimer's Disease Neuroimaging Initiative: progress and plans - Aisen, PS (2010)
The Clinical Core of the Alzheimer's Disease Neuroimaging Initiative (ADNI) has provided clinical, operational and data management support to ADNI since its inception. This paper reviews the activities and accomplishments of the core in support of ADNI aims. These include the enrollment and follow-up of over 800 subjects in the three original cohorts: healthy controls, amnestic MCI (now referred to as late MCI, or LMCI) and mild Alzheimer's disease (AD) in the first phase of ADNI (ADNI 1), with baseline longitudinal clinical and cognitive assessments. These data, when combined with genetic, neuroimaging and cerebrospinal fluid measures, have provided important insights into the neurobiology of the AD spectrum. Further, these data have facilitated the development of novel clinical trial designs. ADNI has recently been extended with funding from an NIH Grand Opportunities (GO) award, and the new ADNI GO phase has been launched; this includes the enrollment of a new cohort, called early MCI (EMCI), with milder episodic memory impairment than the LMCI group. An application for a further 5 years of ADNI funding (ADNI 2) was recently submitted. This funding would support ongoing follow-up of the original ADNI 1 and ADNI GO cohorts, as well as additional recruitment into all categories. The resulting data would provide valuable data on the earliest stages of AD, and support the development of interventions in these critically important populations.